From Trend to Choices: Cognitive Dissonance and Fast-Fashion Consumption Among Indonesian Influencers - Wulan Dewi, Hasandra; Harjoko, Ivone; Febrianno Boer, Rino (Ilomata International Journal of Social Science, 2023)
In 2010, Instagram was introduced as a free photo-sharing app for iOS and Android users, providing a unique platform for sharing life experiences through visual content. This study, spanning five months (July-December 2023), explores the rise of fast fashion consumption and influencer trends in Indonesia. It employs the diffusion model proposed by Beaudoin, Moore, and Goldsmith. Analysis of interview data using NVivo highlights a strong link between the fashion industry and influencers. NVivo enables remote collaboration, allowing individuals from different locations to work on shared data files in real-time. The study emphasizes data collection through structured interviews based on an in-depth examination of influencers. Findings reveal that the high-value nature of fast fashion significantly influences Indonesian influencers, driven by the growing popularity of consumer trends and ongoing style improvements in the fashion industry. However, it emphasizes the importance of recognizing that unquestionably following trends can profoundly shape an individual's lifestyle, echoing previous research on the pivotal role of trends in fashion choices. Overall, the research underscores the substantial impact of trends and influencers on Indonesia's fast fashion landscape.